Regulation of Investor Protection of Information Technology-Based Shari'ah Crowdfunding Services in Indonesia from the Perspective of Shari'ah Economic Law - Fachruddin, Mohammad Reza; Tajrid, Amir; Heradhyaksa, Bagas (SAINTIS Publishing, 2024)
Investor protection is needed in IT-based Islamic crowdfunding services to avoid the use of funds that are not in accordance with the predetermined Budget Plan (RAB) and late sukuk payments by the Issuer. In fact, in the report submitted by PT LBS Urun Dana as the organiser, there are several issuers who are late in paying sukuk. This situation raises concerns and losses for investors. This research aims to see how investor protection arrangements for Information Technology-based Islamic crowdfunding services in Indonesia and how the law of these arrangements in the perspective of Sharia Economic Law. This type of research is qualitative literature research with a juridical-normative approach. Data collection is done through documents. This research concludes that there is no law that contains investor protection regulations in IT-based sharia crowdfunding services. The absence of this law has the potential for non-transparent fund management and misappropriation by the Issuer. Clear regulations to avoid losses so that they are in accordance with the agreed agreement. From the perspective of Islamic economic law, the law on investor protection in Information Technology-based Islamic crowdfunding services is mandatory.